Students' emotional experiences in writing English essays: A thematic narrative analysis - Harnita Rosalia; Andi Nurul Annisa Budiman (Researcher and Lecturer Society, 2026)
This study explores students’ emotional experiences during the process of writing English essays in an EFL context. The study investigates the emotions students encounter, how these emotions influence their writing engagement and performance, and how students construct meaning from their emotional experiences. This qualitative study employed thematic narrative analysis involving five undergraduate students from the English Department at Universitas Negeri Makassar, selected through purposive sampling. Data were collected through semi-structured interviews and four-week reflective journals and analyzed by identifying recurring emotional themes while preserving participants’ narrative experiences and reflections. The findings reveal that students experienced anxiety, self-doubt, motivation, relief, and emotional responses to feedback throughout different stages of writing. These emotions significantly influenced students’ confidence, engagement, and writing performance. The study further found that emotional experiences operated as an interconnected emotional system in which anxiety, confidence, motivation, and feedback responses continuously influenced one another throughout the writing process. In addition, students interpreted anxiety as evidence of linguistic limitations while perceiving improvement and supportive feedback as sources of confidence and motivation. This study contributes to EFL writing research by highlighting the dynamic and interconnected nature of emotional experiences and demonstrating the value of thematic narrative analysis in exploring students’ emotional journeys and meaning-making processes in EFL writing contexts.